ANALYSIS OF GEODESIC METHODS AND REMOTE SENSING DATA FOR FORMING CARTOGRAPHIC SUPPORT FOR URBAN PLANNING DOCUMENTATION - Pilicheva, M.; Danyliuk, A. (Municipal economy of cities. Series: «Economy science», 2025)
The development of urban planning documentation is closely related to ensuring accurate and up-to-date geospatial data. In the process of using modern methods, such as global navigation satellite systems (GNSS), lidar scanning, satellite imagery and aerial photography, numerous issues arise related to the integration of data from different sources, which include: lack of a single methodology for standardization and storage of data; the presence of shortcomings in the accuracy and relevance of geospatial information; low level of interoperability between existing geographic information systems (GIS) and cadastral systems. The purpose of this article is to study and systematize modern remote sensing methods, as well as their role in updating urban planning documentation in comparison with other methods. Particular attention should be paid to aerial photography using unmanned aerial vehicles (UAVs), which are characterized by high image detail, ease of use in local areas and cost-effectiveness. At the same time, we emphasize the need to integrate lidar scanning to create three-dimensional terrain models, which is important for areas with complex terrain or dense development. This article also highlights that automation of data processing and integration of results into geographic information systems is a key factor in increasing the efficiency of updating urban documentation. The article presents the structure of urban planning documentation in Ukraine at the state, regional and local levels, as well as proposes methods for updating its cartographic support. However, in order to fully realize the potential of remote sensing methods, further improvement of the regulatory framework and investments in the development of relevant technologies are necessary. The implementation of these solutions will help create a standardized methodology for supporting mapping that takes into account the specifics of local territories, environmental problems and the needs of sustainable development. This will ensure a high level of planning accuracy, minimize risks and contribute to effective land resource management.